Analisis Pengaruh Harga, Kualitas Pelayanan, Lokasi, Promosi Dan Fasilitas Terhadap Kepuasan Konsumen Pada Semoenailstudio Jember - Yohanes Fredy Wijaya; Haifah; Hayatul Maspufah (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to determine and analyze the partial and simulaneous effect on price,location service quality, promotion and facility on consumen satisfaction at Semoenailsstudio. The research method used is quantitative. The population involve the whole consumen at Semoenailsstudio, the sample was 60 people with purposive sampling. The analysis used includes , classical assumption test, multiple linear regression analysis, determination R2 and hypothesis test. Based on the result of the analysis, this study shows that the F test of the variables of price, location quality, promotion and facility had a simultaneous effect on consumen satisfaction. Meanwhile, the results of the t-test research in this study showed that the variables of service quality had a positive and significant effect on consumen satisfaction . while the variables price , promotion and facility on consumen satisfaction.